Clozapine combined with different antipsychotic drugs for treatment resistant schizophrenia - Barber, S; Olotu, U; Corsi, M; Cipriani, A (John Wiley & Sons, Ltd, 2017)
Background Between 40% and 70% of people with treatment-resistant schizophrenia do not respond to clozapine, despite adequate blood levels. For these people, a number of treatment strategies have emerged, including the prescription of a second anti-psychotic drug in combination with clozapine. Objectives To determine the clinical effects of various clozapine combination strategies with antipsychotic drugs in people with treatment-resistant schizophrenia both in terms of efficacy and tolerability. Search methods We searched the Cochrane Schizophrenia Group's Study-Based Register of Trials (to 28 August 2015) and MEDLINE (November 2008). We checked the reference lists of all identified randomised controlled trials (RCT). For the first version of the review, we also contacted pharmaceutical companies to identify further trials. Selection criteria We included only RCTs recruiting people of both sexes, aged 18 years or more, with a diagnosis of treatment-resistant schizophrenia (or related disorders) and comparing clozapine plus another antipsychotic drug with clozapine plus a different antipsychotic drug. Data collection and analysis We extracted data independently. For dichotomous data, we calculated risk ratios (RRs) and 95% confidence intervals (CI) on an intention-to-treat basis using a random-effects meta-analysis. For continuous data, we calculated mean differences (MD) and 95% CIs. We used GRADE to create 'Summary of findings' tables and assessed risk of bias for included studies. Main results We identified two further studies with 169 participants that met our inclusion criteria. This review now includes five studies with 309 participants. The quality of evidence was low, and, due to the high degree of heterogeneity between studies, we were unable to undertake a formal meta-analysis to increase the statistical power. For this update, we specified seven main outcomes of interest: clinical response in mental state (clinically significant response, mean score/change in mental state), clinical response in global state (mean score/change in global state), weight gain, leaving the study early (acceptability of treatment), service utilisation outcomes (hospital days or admissions to hospital) and quality of life. We found some significant differences between clozapine combination strategies for global and mental state (clinically significant response and change), and there were data for leaving the study early and weight gain. We found no data for service utilisation and quality of life. Clozapine plus aripiprazole versus clozapine plus haloperidol There was no long-term significant difference between aripiprazole and haloperidol combination strategies in change of mental state (1 RCT, n = 105, MD 0.90, 95% CI -4.38 to 6.18, low quality evidence). There were no adverse effect data for weight gain but there was a benefit of aripiprazole for adverse effects measured by the LUNSERS at 12 weeks (1 RCT, n = 105, MD -4.90, 95% CI -8.48 to -1.32) and 24 weeks (1 RCT, n = 105, MD -4.90, 95% CI -8.25 to -1.55), but not 52 weeks (1 RCT, n = 105, MD -4.80, 95% CI -9.79 to 0.19). Similar numbers of participants from each group left the study early (1 RCT, n = 106, RR 1.27, 95% CI 0.72 to 2.22, very low quality evidence). Clozapine plus amisulpride versus clozapine plus quetiapine One study showed a significant benefit of amisulpride over quetiapine in the short term, for both change in global state (Clinical Global Impression (CGI): 1 RCT, n = 50, MD -0.90, 95% CI -1.38 to -0.42, very low quality evidence) and mental state (Brief Psychiatric Rating Scale (BPRS): 1 RCT, n = 50, MD -4.00, 95% CI -5.86 to -2.14, low quality evidence). Similar numbers of participants from each group left the study early (1 RCT, n = 56, RR 0.20, 95% CI 0.02 to 1.60, very low quality evidence) Clozapine plus risperidone versus clozapine plus sulpiride There was no difference between risperidone and sulpiride for clinically significant response, defined by the study as 20% to 50% reduction in Positive and Negative Syndrome Scale (PANSS) (1 RCT, n = 60, RR 0.82, 95% CI 0.40 to 1.68, very low quality evidence). There were similar equivocal results for weight gain (1 RCT, n = 60, RR 0.40, 95% CI 0.08 to 1.90, very low quality evidence) and mental state (PANSS total: 1 RCT, n = 60, MD -2.28, 95% CI -7.41 to 2.85, very low quality evidence). No-one left the study early. Clozapine plus risperidone versus clozapine plus ziprasidone There was no difference between risperidone and ziprasidone for clinically significant response (1 RCT, n = 24, RR 0.80, 95% CI 0.28 to 2.27, very low quality evidence), change in global state CGI-II score (1 RCT, n = 22, MD -0.30, 95% CI -0.82 to 0.22, very low quality evidence), change in PANSS total score (1 RCT, n = 16, MD 1.00, 95% CI -7.91 to 9.91, very low quality evidence) or leaving the study early (1 RCT, n = 24, RR 1.60, 95% CI 0.73 to 3.49, very low quality evidence). Clozapine plus ziprasidone versus clozapine plus quetiapine One study found, in the medium term, a superior effect for ziprasidone combination compared with quetiapine combination for clinically significant response in mental state (> 50% reduction PANSS: 1 RCT, n = 63, RR 0.54, 95% CI 0.35 to 0.81, low quality evidence), global state (CGI - Severity score: 1 RCT, n = 60, MD -0.70, 95% CI -1.18 to -0.22, low quality evidence) and mental state (PANSS total score: 1 RCT, n = 60, MD -12.30, 95% CI -22.43 to -2.17, low quality evidence). There was no effect for leaving the study early (1 RCT, n = 63, RR 0.52, CI 0.05 to 5.41, very low quality evidence). Authors' conclusions The reliability of results from this review is limited, evidence is of low or very low quality. Furthermore, due to the limited number of included studies, we were unable to undertake formal meta-analyses. As a consequence, any conclusions drawn from these findings are based on single, small-sized RCTs with high risk of type II error. Properly conducted and adequately powered RCTs are required. Future trialists should seek to measure patient-important outcomes such as quality of life, as well as clinical response and adverse effects.